Cognitive and Behavioral Effects of Topiramate Versus Carbamazepine Monotherapy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The cognitive and behavioral effects of topiramate (TPM) versus carbamazepine (CBZ) were evaluated in a multicenter, randomized, open-label, parallel-group trial at Sanggye Paik Hospital, Seoul, and other university centers in Korea.